Nanocomposites : in situ synthesis of polymer-embedded nanostructures - Nicolais, Luigi; Carotenuto, Gianfranco (Hoboken, New Jersey : Wiley-Interscience, 2014)
'Structured as a practical lab manual, this book provides detailed descriptions of how polymeric nanocomposites are synthesized, offering the reader an understanding of the principles and techniques involved. Topics covered include: an introduction to the properties and applications of nanocomposite materials; explanation of morphological and topological concepts; theory of phase separation and nanoparticle aggregation; methods for the synthesis of nanocomposites; exercising morphological control; standard characterization techniques and methods for data analysis used in the synthesis of NCs; and related toxicity issues'--
'The two aspects of scCO2 use most relevant to the scope of this book are the processing and synthesis of polymers, and scCO2 generation and impregnation of nanoparticles. These topics will be discussed in greater detail'--
Includes index.
Keywords: Nanostructured materials; Polymeric composites